(untitled) (Current Horticulture, 2024)
The experiment was conducted to evaluate the effect of exogenous EE-GRSP on soil aggregate distribution and root hormone levels under drought stress using controlled potted conditions, at College of Horticulture and Gardening, Yangtze University, Jingzhou, thubei, China. The easily extracted glomalin-related soil protein (EE GRSP) was collected from rhizosphere soil of Satsuma mandarin orchard established on trifoliate orange (Poncirus trifoliata Rafin), at Jingzhou, China. The EE-GRSP solution was exogenously applied weekly into rhizosphere of trifoliate orange exposed to well-watered (WW) and drought stress (DS) under potted conditions. After 41 days, exogenous EE-GRSP significantly increased leaf relative water content under WW and DS, compared with non EE-GRSP treatment. Application of EE-GRSP significantly increased root gibberellins, methyl-jasmonate (MeJA), zeatin riboside (ZR), and brassinosteroids (BRs) concentrations under WW and DS conditions over non-EE-GRSP treatment. Rhizosphere soil of EE-GRSP-treated seedlings showed a much higher distribution of water-stable aggregates in different sizes of 2.00-4.00, 1.00-2.00, 0.50-1.00, and 0.25-0.50 mm and soil greater mean weight diameter, compared to non-EE-GRSP-treated control, regardless of soil water status. These results suggested that exogenous EE-GRSP enhanced the drought tolerance of trifoliate orange seedlings by promoting soil aggregation and hormonal level of roots.